Adsorptive removal ofPb(II) ion from aqueous solution using rice husk-based activated carbon - ROSMAN, AHMAD SHAKEEL (Universiti Teknologi PETRONAS, 2012)
There are various methods can be used to remove heavy metals from waste water, such as chemical precipitation, ion exchange, electroplating and membrane separation. Nevertheless the most effective method would be adsorption using activated carbon due to its large number of pores. This project will be focusing primarily on rice husk as potential activated carbon as low cost adsorbent to remove Pb(II) from wastewater. Preparation of activated carbon involves three steps which are raw rice husk preparation, activation stage and carbonization stages. Preparation of rice husk involves grinding to 63 !liD which is then treated with 1.0 M of sodium hydroxide (NaOH). The treated rice husk is then carbonized at 500°C for 2 hours to remove volatile organic components. After the activated carbons are produced, extraction study will be carried out to further study the adsorption capacity. The pores development of the rice husk was analysed using Field Emission Scanning Electron Microscope (FESEM). Other analyses for rice husk based activated carbon were conducted using TGA, XRD, CHN Elemental Analyser and FTIR for characterisation study on the particles of rice husk. Pb(II) ion extraction from aqueous solution was done using rice husk based activated carbon which was conducted at different contact time at room temperature. The adsorption capacity of Pb(II) ion was determined using Atomic Adsorption Spectroscopy (AAS). Results obtained from adsorption study indicate that rice has the potential to be used as adsorbent for heavy metals removal.